Permasalahan Investasi Bodong Berbasis Online di Indonesia - John jotham Terrance; Diana Putong; Arthur Novy Tuwaidan (Lembaga Penelitian dan Pengabdian Universitas Negeri Manado, 2022)
In investing, most people will try to make investments such as investing in stocks, property, saving in banks, even forex trading and others because what they know is that there are so many benefits from investing. It turns out that the ease of investing using only mobile devices has a positive but also a negative impact, many parties are taking advantage of this momentum to seek their own profit by creating